2015
DOI: 10.5152/balkanmedj.2015.15487
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Posterior Leukoencephalopathy Syndrome Due to Carboplatin and Paclitaxel Therapy

Abstract: Background: Reversible posterior leukoencephalopathy syndrome (RPLS) is a clinicoradiologic syndrome characterized by headache, decreased alertness, seizures, visual abnormalities, and white matter changes indicative of cerebral edema. Although the pathogenesis remains poorly understood, several etiological causes have been described. RPLS is a common complication of chemotherapeutics because of its toxic effect on the central nervous system. This syndrome is frequently associated with seizures but rarely seen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
0
5
1
Order By: Relevance
“… 9 , 14 Unfortunately, 1 patient died because of progression of the primary disease. 11 In contrast, in our patient, seizures did not recur over the subsequent 3 months, and no neurological deficits were observed.…”
contrasting
confidence: 73%
“… 9 , 14 Unfortunately, 1 patient died because of progression of the primary disease. 11 In contrast, in our patient, seizures did not recur over the subsequent 3 months, and no neurological deficits were observed.…”
contrasting
confidence: 73%
“…Through our literature review, we identified 19 cases of patients experiencing PRES following the administration of chemotherapy drugs with or without targeted therapies, as detailed in Table 1 . 1 4 , 6 15 …”
Section: Discussionmentioning
confidence: 99%
“…Hypertension, (pre)eclampsia, hypercalcemia, renal diseases, inflammatory, and autoimmune disorders are the most common underlying conditions . PRES can also manifest after exposure to a number of therapeutic agents, particularly immunosuppressants and cytotoxic agents . Patient‐2 developed PRES following paclitaxel‐carboplatin combination therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Patient‐2 developed PRES following paclitaxel‐carboplatin combination therapy. The toxicity of platinum analogues has been reported primarily in association with cisplatin, very rarely with carboplatin …”
Section: Discussionmentioning
confidence: 99%